Networks and Practices of Connoisseurship in the Global Eighteenth Century (De Gruyter, 2024)
The 18th century was the age of the connoisseur. It was also an era of an expanding global consciousness born of accelerating trade and imperial conquest. This volume puts into dialogue the consolidation of connoisseurship as an empirical mode of artistic analysis in Europe and Asia and the increasing exposure to different modes of artmaking facilitated by local and global networks over the course of the long 18th century. Focusing on exchanges between India, Japan, China and Europe, the contributors to this volume examine the complex and nuanced impacts on connoisseurial practice of encounters with artworks from different regions of the globe, the international networks that made those encounters possible, and the intricate transactions through which connoisseurial knowledge of art was generated. Expansive focus on practices and networks in India, Japan, and Europe in the 18th century Complexities and asymmetries of connoisseurship in an expanding world ; The 18th century was the age of the connoisseur. It was also an era of an expanding global consciousness born of accelerating trade and imperial conquest. This volume puts into dialogue the consolidation of connoisseurship as an empirical mode of artistic analysis in Europe and Asia and the increasing exposure to different modes of artmaking facilitated by local and global networks over the course of the long 18th century. Focusing on exchanges between India, Japan, China and Europe, the contributors to this volume examine the complex and nuanced impacts on connoisseurial practice of encounters with artworks from different regions of the globe, the international networks that made those encounters possible, and the intricate transactions through which connoisseurial knowledge of art was generated. Expansive focus on practices and networks in India, Japan, and Europe in the 18th century Complexities and asymmetries of connoisseurship in an expanding world ; Das 18. Jahrhundert war das Zeitalter der Kunstkenner:in und zugleich Ära eines globalen Bewusstseins, das aus dem sich beschleunigenden Handel und imperialen Eroberungen hervorging. Diese Publikation bringt die Kennerschaft, die sich als empirische Methode der Kunstanalyse in Europa und Asien etablierte, in einen Dialog mit der zunehmenden Auseinandersetzung mit unterschiedlichen Formen des Kunstschaffens, die im Verlauf des langen 18. Jahrhunderts durch lokale und globale Netzwerke ermöglicht wurde. Die Autor:innen des Buches nehmen Wechselbeziehungen zwischen Indien, Japan, China und Europa in den Blick und untersuchen, wie sich Begegnungen mit Kunstwerken aus verschiedenen Regionen der Welt auf die Praxis der Kunstkennerschaft in Asien und Europa auswirkten. Praktiken und Netzwerke in Indien, Japan und Europa des 18. Jahrhunderts Komplexität und Asymmetrien der Kunstkennerschaft in einer expandierenden Welt